The Breezy Batik Perfect-10 Carry All: promoting safe travel behaviour - Ngali, Norzaidah; Rahmat, Norazlina; Ramli, Noorazlin; Abd Ghani, Fatimah; Nik Dzulkefli, Nik Nur Shaadah (Academica Press Solutions, 2023)
The Breezy Batik Perfect-10 Carry All is a versatile and innovative travel bag designed to support safe behaviour among travellers, especially during the endemic phase. It encourages travellers to bring and use their own belongings when using public services such as mosques or musolla at the shopping malls or R&R. By providing a reliable means of carrying personal belongings, the Carry All aims to foster confidence and ease in travellers while reinforcing safe practices. The Breezy Batik Perfect-10 Carry All is a bag that boasts several unique features catering to the needs of various users. It has a designated compartment for COVID-19 essentials, such as masks and hand sanitizers, and a separate compartment for telekung and sejadah, which caters to Muslim women's needs. Additionally, the bag has interior lighting and a key holder, which makes accessing belongings more convenient, and there is ample space for storing personal items. The bag's versatility makes it practical for travel and daily errands or formal events. Moreover, the lightweight design and cultural significance make it a valuable addition to any wardrobe, suitable for people of all genders. A market survey was conducted using convenience sampling via social media to gather feedback from potential buyers on the Breezy Batik Perfect-10 Carry All. The survey received 117 responses, with 79.5% of respondents indicating interest in purchasing the travel bag. The top-ranked factor for intention to buy the bag was the convenience of having all travel essentials in one bag, selected by 75.2% of respondents. These findings suggest a positive perception and high acceptance of the Breezy Batik Perfect-10 Carry All among potential buyers. The bag was crafted by disabled individuals at PPDK Wakaf TAPAI, Terengganu, using batik fabric to showcase practicality and cultural heritage with a focus on a lightweight design. The collaboration with PPDK Wakaf TAPAI promotes sustainable cultural, social, and economic development in the local community, aligning with Sustainable Development Goals (SDGs). This initiative demonstrates a successful model of community-based sustainable development and positions the Carry All as a travel impulse item.